Bridging the State and Society: Legislative Recess, Public Aspirations, and Institutional Mediation in Subnational Indonesia - Luh Lisna Aprilia; I Putu Dharmanu Yudartha (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
This article examines legislative recess practices of Regional People’s Representative Councils (DPRD) as a mechanism mediating state–society relations in subnational Indonesia. It investigates how public aspirations are articulated, filtered, and institutionalized through recess activities, and assesses whether these practices function as substantive democratic mediation or merely symbolic rituals. Drawing on a qualitative case study of the Bali Provincial DPRD, the study employs in-depth interviews with legislators, DPRD Secretariat officials, and community representatives, alongside document analysis of recess reports, meeting records, and regulatory frameworks. Data were analyzed thematically using perspectives from political sociology and governance studies. This article makes three novel contributions. First, it reconceptualizes legislative recess as a form of institutional mediation rather than a procedural extension of legislative representation. Second, it empirically demonstrates the central role of supporting bureaucracies—particularly the DPRD Secretariat—as active mediators shaping the translation of public aspirations into policy outcomes. Third, it advances a relational understanding of subnational democracy by revealing how symbolic representation and material governance processes intersect to reproduce participatory inequalities. The findings show that the effectiveness of recess practices is contingent upon institutional capacity, budgetary constraints, and uneven political literacy. Strengthening mediating institutions and inclusive participation is therefore essential for enhancing democratic governance at the subnational level.